2011
DOI: 10.1093/jxb/erq416
|View full text |Cite
|
Sign up to set email alerts
|

ABC transporters coordinately expressed during lignification of Arabidopsis stems include a set of ABCBs associated with auxin transport

Abstract: The primary inflorescence stem of Arabidopsis thaliana is rich in lignified cell walls, in both vascular bundles and interfascicular fibres. Previous gene expression studies demonstrated a correlation between expression of phenylpropanoid biosynthetic genes and a subset of genes encoding ATP-binding cassette (ABC) transporters, especially in the ABCB/multi-drug resistance/P-glycoprotein (ABCB/MDR/PGP) and ABCG/pleiotropic drug resistance (ABCG/PDR) subfamilies. The objective of this study was to characterize t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
130
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 151 publications
(135 citation statements)
references
References 50 publications
4
130
0
Order By: Relevance
“…The hypothesis was that monolignol glucosides would be stored in the vacuole or transported from the cytosol to the cell wall and then deglucosylated by b-glucosidases before their polymerization in muro (Freundenberg et al, 1952;Sarkanen, 1971). However, recent studies suggest that the monolignol glucosides could be, at least in angiosperms, a storage form of the monolignols and not their direct transportation form (Miao and Liu, 2010;Kaneda et al, 2011;Liu et al, 2011;Liu, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The hypothesis was that monolignol glucosides would be stored in the vacuole or transported from the cytosol to the cell wall and then deglucosylated by b-glucosidases before their polymerization in muro (Freundenberg et al, 1952;Sarkanen, 1971). However, recent studies suggest that the monolignol glucosides could be, at least in angiosperms, a storage form of the monolignols and not their direct transportation form (Miao and Liu, 2010;Kaneda et al, 2011;Liu et al, 2011;Liu, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…As substrate specificities cannot easily be deduced from sequence Murphy 2006, Bailly et al 2011), it is currently unclear how many of the 17 remaining ABCBs function as auxin transporters. However, a recent publication suggested that there are eventually more to come: ABCB14 and ABCB15, both apparently involved in stem lignification, promote auxin transport since inflorescence stems in both mutants showed a reduction in PAT (Kaneda et al 2011) (see Fig. 1).…”
Section: Abcb Expression and Roles During Polar Auxin Transportmentioning
confidence: 94%
“…ABCB11, ABCG29, and ABCG33 transporters were previously identified as candidate monolignol exporters (Ehlting et al, 2005;Kaneda et al, 2011;Alejandro et al, 2012). To test the hypothesis that these putative monolignol transporters could have a restricted plasma membrane localization adjacent to secondary cell wall domains, GFP translational fusions of ABCB11, ABCG29, and ABCG33 were transformed into VND7-VP16-GR plants.…”
Section: Abc Transporters Localize To All Plasma Membrane Domains Durmentioning
confidence: 99%